Gli anziani e la domanda di città - Carrera, Letizia (SocietàMutamentoPolitica, 2020)
The process of the increasing number of elderly people is linked with the important change of social representations of third age. Elderly people forcefully claim a new urban protagonism. They look at the city to satisfy not only their needs but also the conditions for their existential planning.